Regionale Prosodie im Deutschen : Variabilität in der Intonation von Abschluss und Weiterverweisung - Gilles, Peter (Linguistik, Impulse & Tendenzen ;, 2005)
In this phonetic study, a systematic analysis of intonation from eight German regional varieties is presented for the first time, in which the numerous phonetic forms and their functions in conversation are described. The accompanying CD-ROM includes a co.